Correlation between objective and subjective measures of the physical activity in women with urinary incontinence (Research, Society and Development, 2021)
Urinary incontinence (UI) can lead the individual to abandon social activities and reduce physical activity, as there is fear of urine loss happening in public. The level of physical activity can be measured objectively, more reliably, but at a higher cost or subjectively, performed on a large scale, but with less accurate results. The aim of the present study was to correlate the objective and subjective measures of the level of physical activity in women with urinary incontinence. This is a cross-sectional study composed of women complaining of involuntary loss of urine who were asked to complete the international physical activity questionnaire (IPAQ) - Short version and to use the motion monitor (Fitbit Charge 3) for 7 days, for the evaluation of subjective and objective measures. The study consisted of 66 volunteers, aged 57.7 ± 11.2 years, body mass index (BMI) = 29.1 ± 4.2 kg/m2 and 46.9% (n = 31) of the participants presented moderate UI severity. There was no correlation between objective and subjective measures in light (r = 0.0219, p = 0.863), moderate (r = 0.0331, p = 0.794) and vigorous (r = 0.0072; p = 0.955) activities. According to the results, in the group of women with urinary incontinence, there is no correlation between the objective and subjective measures of the level of physical activity.